The effect of depression and side effects of antiepileptic drugs on injuries in patients with epilepsy. (20th July 2017) - Gur‐Ozmen, S.; Mula, M.; Agrawal, N.; Cock, H. R.; Lozsadi, D.; von Oertzen, T. J.
Abstract : Background and purpose: People with epilepsy are at increased risk of accidents and injuries but, despite several studies on this subject, data regarding preventable causes are still contradictory. The aim of this study was to investigate the relationship between injuries, side effects of antiepileptic drugs (AEDs) and depression. Methods: Data from a consecutive sample of adult patients with epilepsy attending the outpatient clinics at St George's University Hospital in London were included. All patients were asked if they had had any injury since the last clinic appointment and completed the Liverpool Adverse Event Profile (LAEP) and Neurological Disorders Depression Inventory for Epilepsy. Results: Among 407 patients (243 females, mean age 43.1 years), 71 (17.4%) reported injuries since the last appointment. A two‐step cluster analysis revealed two clusters with the major cluster (53.5% of the injured group) showing a total score for LAEP ≥45, a positive Neurological Disorders Depression Inventory for Epilepsy screening and presence of AED polytherapy. A total score for LAEP ≥45 was the most important predictor. Conclusions: Antiepileptic drug treatment should be reviewed in patients reporting injuries in order to evaluate the potential contribution and burden of AED side effects.